2020
DOI: 10.5435/jaaos-d-19-00718
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-day Outcomes After Surgery for Metastatic Bone Disease of the Extremities

Abstract: Introduction: Metastatic bone disease of the extremities is a notable cause of morbidity and mortality. Surgical management is not curative; therefore, risks and benefits of surgery must be carefully considered. Previous studies of surgical outcomes are limited by small sample sizes because of the rare incidence of these procedures. In this study, we aim to describe the rates of complications and mortality in the first 30 days after surgical treatment of metastatic bone disease of the femur and hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Several recent articles have analyzed aspects of the care of patients with these diseases. Gallaway et al performed a national database review of morbidity and mortality after surgical procedures for metastatic disease of the humerus and femur; the 30-day mortality was 7.1%, with postoperative complications and morbidity being common 21 . These authors observed significantly lower risks of revision and complications with prophylactic surgery, highlighting the value of identifying and treating these patients early in the course of the disease and adding to the literature supporting prophylactic surgery.…”
Section: Metastatic Diseasementioning
confidence: 99%
“…Several recent articles have analyzed aspects of the care of patients with these diseases. Gallaway et al performed a national database review of morbidity and mortality after surgical procedures for metastatic disease of the humerus and femur; the 30-day mortality was 7.1%, with postoperative complications and morbidity being common 21 . These authors observed significantly lower risks of revision and complications with prophylactic surgery, highlighting the value of identifying and treating these patients early in the course of the disease and adding to the literature supporting prophylactic surgery.…”
Section: Metastatic Diseasementioning
confidence: 99%
“…Skeletal complications of metastatic bone disease include bone pain, pathologic fracture, decreased quality of life, bone marrow aplasia, and hypercalcemia of malignancy. 1 Metastatic carcinoma is the most common malignancy treated by orthopaedic surgeons. Treatment of bone lesions is very important for these patients with regard to quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with surgically treated skeletal metastases, the incidence rate of thromboembolic complications is even higher, despite thromboprophylaxis. Their rate for deep venous thrombosis (DVT) is 2-11%; and that of pulmonary embolism (PE) 2-9%, and for lethal PE under 1% to over 3% [1,[8][9][10][11]. The overall postoperative mortality rate is high, ranging from more than 7% during the first 30 days to between 38 and 47% at 1 year [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Their rate for deep venous thrombosis (DVT) is 2-11%; and that of pulmonary embolism (PE) 2-9%, and for lethal PE under 1% to over 3% [1,[8][9][10][11]. The overall postoperative mortality rate is high, ranging from more than 7% during the first 30 days to between 38 and 47% at 1 year [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%